Interleukin-1 Receptor-Associated Kinase-3 Aggravates Neuroinflammatory Injury After Intracerebral Hemorrhage via Activation NF-κB/IL-17A Pathway in Mice - Wang J; Li Y; Tan C; Shao J; Tang W; Kong Q; Sheng W; Ding Z; Li F; Piao J; Lv D; Hu L; et al. (Journal of Inflammation Research)
Jun Wang,1,* Yulong Li,1,* Chunyu Tan,1,* Jinlian Shao,1 Weitai Tang,2 Quan Kong,3 Wenqianjun Sheng,1 Zhiquan Ding,1 Feng Li,1 Jifeng Piao,1 Dingyi Lv,1 Libin Hu,1 Qinghua Wang,1 Xiaodan Jiang1 1Neuromedicine Center, The National Key Clinical Specialty, The Engineering Technology Research Center of Education Ministry of China on Diagnosis and Treatment of Cerebrovascular Disease, Guangdong Provincial Key Laboratory on Brain Function Repair and Regeneration, The Neurosurgery Institute of Guangdong Province, Guangdong-Hong Kong-Macao Greater Bay Area Center for Brain Science and Brain-Inspired Intelligence, Zhujiang Hospital, Southern Medical University, Guangzhou, 510282, People’s Republic of China; 2Department of Neurosurgery, The People’s Hospital of Luoding & Affiliated Luoding Hospital of Guangdong Medical University, Luoding, 527200, People’s Republic of China; 3Neurosurgery Department of Zengcheng Campus, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qinghua Wang; Xiaodan Jiang, Email wqh1123@126.com; jiangxiao_dan@163.comBackground: Neuroinflammatory reactions are crucial factors in secondary brain damage following intracerebral hemorrhage (ICH). Although previous studies have shown that IRAK3 is involved in immune responses, the potential effects of IRAK3 on ICH remain unclear.Methods: Collagenase IV–induced ICH mouse model. Western blotting was used to determine the expression of IRAK3 at different time points following ICH. Immunofluorescence was used to investigate the cellular localization of IRAK3. The ICH model was treated with recombinant human IRAK3 (rh-IRAK3) or IRAK3 siRNA via an intracerebroventricular injection. The effect of IRAK3 on ICH mice was assessed by Western blotting and short-term and long-term neurological function evaluation. RNA-seq was performed to explore the mechanism by which IRAK3 promotes inflammation after ICH. The mechanisms of IRAK3 and neuroinflammation will be further investigated by Western blotting, qRT-PCR and immunofluorescence. Recombinant IL-17A was used to investigate the connection between IRAK3 and the NF-κB/IL-17A signaling pathway in vivo and in vitro experiments.Results: The expression of IRAK3 increased, peaking at 24 h, followed by a subsequent decrease after ICH. IRAK3 is mainly expressed in the microglia. RNA-seq analysis revealed 1,797 differentially expressed genes around the perihematomal brain tissue after IRAK3 siRNA treatment, with multiple inflammatory pathways being downregulated. Rh-IRAK3 treatment resulted in upregulation of the levels of inflammatory cytokines around the perihematomal tissue and exacerbated neurological function deficits. Furthermore, IRAK3 siRNA treatment markedly decreased the expression of inflammatory cytokines and microglial activation via the NF-κB/IL-17A signaling pathway. Recombinant IL-17A exacerbated the inflammatory response in vivo and in vitro; however, IRAK3 knockdown reversed this process.Conclusion: IRAK3 aggravates neuroinflammation by activating the NF-κB/IL-17A signaling pathway, thereby exacerbating neurological deficits following ICH. Therefore, inhibition IRAK3 may be a promising approach for treating ICH.Keywords: IRAK3, neuroinflammation, intracerebral hemorrhage, microglia, NF-κB/IL-17A pathway